Economía circular como desarrollo sostenible, reciclaje y medio ambiente en el GAD municipal del cantón Junín, año 2022 - Bermeo Bravo, Andy Natalí (2024)
The purpose of this research was to analyze the circular economy as sustainable development, recycling and the environment in the Municipal GAD of the Junín canton. This research is descriptive, not experimental, so it was necessary to apply synthetic, deductive-inductive analytical methods. To achieve the object of study, the methodological proposal was made, which is based on three research phases; the first to the elaboration of the state of the art of the variables under study, as well as the advantages implied by the application of a circular economy model. The second phase responds to the situational diagnosis, for which it was necessary to conduct an interview with the head of the Environmental Department of the GAD and president of the recyclers of the Junín canton, with the response that said economic model has not been implemented, in addition to the application of a survey aimed at 365 citizens, showing that it is unknown what the circular economy entails and what the corresponding processes are for adequate waste management. Finally, in the third phase, the pilot plan is proposed, defining each of the necessary strategies that will contribute to fulfilling the purpose of the research and mitigating the main problems identified. Therefore, it is necessary for the Junín cantonal GAD to apply this pilot plan since through it they will be able to contribute to the town achieving sustainable development while taking care of the environment.